Inovasi Pembelajaran Bahasa Indonesia Melalui Pendekatan Proses - Hazril Fikri Anwar; Edi Syaputra (Universitas Dehasen Bengkulu, 2022)
Nowadays, there are still many teachers who use theoretical and rote learning techniques. So that learning activities tend to be rigid, monotonous, and boring. Especially in Indonesian language lessons, the material presented is in fact still not able to attach to students as something rational, cognitive, and effective. The assumption so far that learning Indonesian language and literature is easy has actually caused the failure of several students who took the National Examination (UN). As a result, sometimes students are not enthusiastic about studying Indonesian language and literature. In essence, learning Indonesian language and literature in schools is shown to raise the awareness of students, teachers, administration and school principals towards the existence of Indonesian language and literature as a means of communication and as a unifying tool for this nation. Innovative Indonesian language lessons pay close attention to the competencies and rights of students, so it can be said that innovative Indonesian language learning is humanist language learning. In connection with that, the goal that is owned and achieved is that Indonesian language teachers must be able to realize innovative learning models so that Indonesian language learning becomes a fun and easy lesson to follow. The results of the study have broad implications for Indonesian language teachers in schools to realize innovative Indonesian language learning to always provide variety in learning by utilizing the competencies possessed by students.